2002
DOI: 10.1080/16501970213238
|View full text |Cite
|
Sign up to set email alerts
|

External power output changes during prolonged cycling with electrical stimulation

Abstract: This study analysed external power output and physiologic responses in 5 individuals with paraplegia during 40 minutes of electrical stimulation leg cycle exercise. Cycling was performed on a motor-driven isokinetic ergometer that enabled precise determinations of power output. Electrical stimulation was increased to 120-140 mA within the first 5 minutes and remained constant thereafter. Power output increased to 10.7 +/- 3.0 W after 2 minutes, dropped to 5.3 +/- 1.8 W after 6 minutes and subsequently recovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 11 publications
6
21
0
1
Order By: Relevance
“…Theisen et al [12], for example, have shown that efficiency can vary considerably during prolonged, constant-stimulation FES-cycling exercise. In a study with 5 SCI subjects they demonstrated that the net efficiency progressively increased up to a maximum of almost 9% after 40 min.…”
Section: Introductionmentioning
confidence: 99%
“…Theisen et al [12], for example, have shown that efficiency can vary considerably during prolonged, constant-stimulation FES-cycling exercise. In a study with 5 SCI subjects they demonstrated that the net efficiency progressively increased up to a maximum of almost 9% after 40 min.…”
Section: Introductionmentioning
confidence: 99%
“…In a parallel investigation to the development of the iFES-LCE system, Theisen and coworkers (19) observed that cycling with the iFES-LCE at 50 rev/ min invoked a significant cardiorespiratory stimulus, including exercise-induced increases of heart rate and oxygen uptake. Further experimental research is required to compare the magnitude of the cardiorespiratory response induced by the iFES-LCE with that produced by presently available commercial FES-LCE systems.…”
Section: Discussionmentioning
confidence: 98%
“…This, together with the weakness of paralysed muscle, results in low power output (Glaser et al 1989;Raymond et al 2002;Theisen et al 2002). It has been argued (Glaser et al 1989) that the low efficiency of stimulated cycling is of little consequence in the context of stationary ergometry since a key objective is to elicit metabolic and cardiopulmonary responses, while the external energy output is not harnessed to do useful external work.…”
Section: Paraplegic Cyclingmentioning
confidence: 96%